Elementary particles under the lens of the black holes - Matsas, George Emanuel Avraam [UNESP] (Sociedade Brasileira de Física, 2004)
After a brief review of the historical development and CLASSICAL properties of the BLACK HOLES, we discuss how our present knowledge of some of their QUANTUM properties shed light on the very concept of ELEMENTARY PARTICLE. As an illustration, we discuss in this context the decay of accelerated protons, which may be also relevant to astrophysics.